The Regulation and Function of Histone Crotonylation - Ntorla, Angeliki; Burgoyne, Joseph Robert (Frontiers in Cell and Developmental Biology, 2021)
Histone crotonylation is a newly identified epigenetic modification that has a pronounced ability to regulate gene expression. It belongs to an expanding group of short chain lysine acylations that also includes the extensively studied mark histone acetylation. Emerging evidence suggests that histone crotonylation is functionally distinct from histone acetylation and that competition for sites of modification, which reflects the cellular metabolic status, could be an important epigenetic mechanism that regulates diverse processes. Here, we discuss the enzymatic and metabolic regulation of histone crotonylation, the “reader” proteins that selectively recognise this modification and translate it into diverse functional outcomes within the cell, as well as the identified physiological roles of histone crotonylation, which range from signal-dependent gene activation to spermatogenesis and tissue injury.